在Excel2003中,若把单元格F2中的公式"=sum($B2:$E2)"移动并粘贴到G3中,则G3中的公式为()。A.=sum($B2:$E2)B.=sum($C3:$F3)C.=sum($B3:$E3...
在Excel2003中,若把单元格F2中的公式"=sum($B2:$E2)"移动并粘贴到G3...[98%]
在Excel2003中,若把单元格F2中的公式"=sum($B2:$E2)"移动并粘贴到G3中,则G3中的公式为()。A.=sum($B2:$E2)B.=sum($C3:$F3)C.=sum($B3:$E3...
在Excel2003中,若把单元格F2中的公式"=sum($B2:$E2)"复制并粘贴到G3...[97%]
在Excel2003中,若把单元格F2中的公式"=sum($B2:$E2)"复制并粘贴到G3中,则G3中的公式为()。A.=sum(B$3:E$3)B.=sum($C3:$F3)C.=sum($B3:$E3...
在Excel2003中,若把单元格F2中的公式"=sum($B2:$E2)"复制并粘贴到G3...[97%]
在Excel2003中,若把单元格F2中的公式"=sum($B2:$E2)"复制并粘贴到G3中,则G3中的公式为()。A.=sum(B$3:E$3)B.=sum($C3:$F3)C.=sum($B3:$E3...
在Excel2003中,若把单元格F2中的公式"=sum($B2:$E2)"复制并粘贴到G3...[97%]
在Excel2003中,若把单元格F2中的公式"=sum($B2:$E2)"复制并粘贴到G3中,则G3中的公式为()。A.=sum(B$3:E$3)B.=sum($C3:$F3)C.=sum($B3:$E3...
在Excel2003中,若把单元格F2中的公式"=sum($B2:$E2)"复制并粘贴到G3...[97%]
在Excel2003中,若把单元格F2中的公式"=sum($B2:$E2)"复制并粘贴到G3中,则G3中的公式为()。A.=sum(B$3:E$3)B.=sum($C3:$F3)C.=sum($B3:$E3...
在Excel2003中,若把单元格F2中的公式"=sum($B$2:$E$2)"复制并粘贴到G3...[97%]
在Excel2003中,若把单元格F2中的公式"=sum($B$2:$E$2)"复制并粘贴到G3中,则G3中的公式为()。A.=sum($B2:$E2)B.=sum($B$2:$E$2)C.==sum($B$3...
在Excel2003中,若把单元格F2中的公式"=sum($B$2:$E$2)"复制并粘贴到G3...[97%]
在Excel2003中,若把单元格F2中的公式"=sum($B$2:$E$2)"复制并粘贴到G3中,则G3中的公式为()。A.=sum($B2:$E2)B.=sum($B$2:$E$2)C.==sum($B$3...
在Excel2003中,若把单元格F2中的公式"=sum($B$2:$E$2)"复制并粘贴到G3...[97%]
在Excel2003中,若把单元格F2中的公式"=sum($B$2:$E$2)"复制并粘贴到G3中,则G3中的公式为()。A.=sum($B2:$E2)B.=sum($B$2:$E$2)C.==sum($B$3...
在Excel2003中,若把单元格F2中的公式"=sum($B$2:$E$2)"复制并粘贴到G3...[97%]
在Excel2003中,若把单元格F2中的公式"=sum($B$2:$E$2)"复制并粘贴到G3中,则G3中的公式为()。A.=sum($B2:$E2)B.=sum($B$2:$E$2)C.==sum($B$3...